Bifunctional nanoparticulated nickel ferrite thin films: Resistive memory and aqueous battery applications. (March 2021) - Dongale, Tukaram D.; Khot, Sagar S.; Patil, Akshay A.; Wagh, Siddhesh V.; Patil, Prashant B.; Dubal, Deepak P.; Kim, Tae Geun
Abstract: Herein, excellent non-volatile memory and aqueous battery properties of solution-processable nickel ferrite (NFO) nanomaterial were demonstrated. In the case of non-volatile memory property, the device operates on ±2 V resistive switching voltage and shows double valued charge-magnetic flux characteristics. Excellent endurance (10 3 ) and retention (10 4 s) non-volatile memory properties with a good memory window (10 3 ) were observed for NFO memristive device. The conduction and resistive switching mechanisms based on experimental data are provided. Furthermore, the present work investigates the electrochemical performance of the NFO thin film electrode in the different electrolytes (viz. Na2 SO4, Li2 SO4, and Na2 SO4 : Li2 SO4 ). It was revealed that the NFO thin film shows improved electrochemical performance in Na2 SO4 electrolyte with a high specific capacity of 18.56 mAh/g at 1 mA/cm 2 current density. The electrochemical impedance spectroscopic results reveal that the NFO thin film electrode shows low series and charge transfer resistance values for Na2 SO4 electrolyte than other electrolytes. The diffusion coefficient of different ions (DNa+, DLi+ and DNa+:Li+ ) were found to be 9.975 × 10 −10 cm 2 s −1, 3.292 × 10 −11 cm 2 s −1, 2 × 10 −10 cm 2 s −1, respectively. A high diffusion coefficient was found for Na + ions, indicating rapid Na + transport with NFO thin-film electrodes Graphical abstract: Unlabelled Image Highlights: Nickel ferrite (NFO) for resistive memory and aqueous battery applications. Resistive switching device shows memristive double valued q-φ characteristics. The memory device shows good endurance, retention, and memory window. NFO electrode shows a high specific capacity of 18.56 mAh/g. Rapid transport of Na + ions due to its high diffusion coefficient.